2009
DOI: 10.1021/om900751f
|View full text |Cite
|
Sign up to set email alerts
|

New POCN-Type Pincer Complexes of Nickel(II) and Nickel(III)

Abstract: Unsymmetrical POC(H)N-type pincer ligands react with NiBr2(NCMe) x to give the complexes (POCN)NiIIBr (POCN= κ P ,κ C ,κ N -{2-(i-Pr2PO),6-(NR2CH2)-C6H3}; NR2= 3-morpholino (3a), NMe2 (3b), and NEt2 (3c)). The presence of an added base such as NEt3 in these metalation reactions maximizes the yields of the target pincer complexes by suppressing the formation of side-products arising from protonation of the ligand by the in situ-generated HBr. The cyclic voltammograms of 3 exhibit a quasi-reversible, one-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 74 publications
6
62
0
Order By: Relevance
“…The bromide complex (κ 3 -15c5 NCOP iPr )Ni(Br) (1-15c5) was isolated in high yield using this procedure adapted from Zargarian, who reported the first nickel NCOP complexes using related ligands featuring simple secondary or tertiary amine donors. 33,34 Full synthetic details are provided in the Experimental Section; accompanying spectra can be found in the Supporting Information (SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The bromide complex (κ 3 -15c5 NCOP iPr )Ni(Br) (1-15c5) was isolated in high yield using this procedure adapted from Zargarian, who reported the first nickel NCOP complexes using related ligands featuring simple secondary or tertiary amine donors. 33,34 Full synthetic details are provided in the Experimental Section; accompanying spectra can be found in the Supporting Information (SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8 More than three decades ago, van Koten et al have shown that the pincer NCN -ligand can support organometallic Ni III complexes that are surprisingly stable, 9 as reported also later for a related pincer system. 10 Moreover, Hillhouse et al 11 and recently Zargarian et al 12 have reported oxidatively-induced reductive elimination of ethers from metallacyclic Ni(alkoxo)(alkyl) and Ni(alkoxo)(aryl) complexes, respectively, however no high-valent Ni species were detected in these cases. Recently, our group has employed the tetradentate ligand N,N'-di-tert-butyl-2,11-diaza[3.3](2,6)-pyridinophane ( tBu N4) to isolate organometallic Ni III complexes that undergo C-halide and C-C bond formation reactions and are active catalysts for Kumada and Negishi coupling reactions.…”
mentioning
confidence: 96%
“…Since our previous report on the phosphorus-containing non-symmetric O,C,S-coordinating pincer-type ligand {3-tBu-5-[P(S)Ph 2 ]C 6 H 3 }P(O)(OiPr) 2 [1] a number of novel such pincer-type ligands have been published and randomly selected examples are shown in Scheme 1. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The classic pincer-type ligands are based on aromatic backbones to which the donor functions are linked by spacers of different lengths. The steric and electronic properties as well as the reactivity of these pincer-type ligands can be controlled by variation of the donor atoms, the substituents attached to the latter, and by functionalization of the aromatic backbones.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Among the pincer-type ligands there are only a few representatives with a redox-active ferrocene backbone (Scheme 2). In 2002, van Koten und Brown presented the first potentially P,C,P-coordinating elemental iodine was observed, providing the ammonium salt [η 5 -CpFeη 5 -C 5 H 2 -1-SnPh 2 I-2-P(O)Ph 2 -5-CH 2 NHMe 2 ]I (8). The compounds are characterized by elemental analyses, 1 H, 13 C, 31 P, 119 Sn NMR spectroscopy, electrospray ionization mass spectrometry, and single-crystal X-ray diffraction analyses (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%